Giant spider & me : a post-apocalyptic tale. 2 - Morino, Kikori; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, LLC, 2018)
"Nagi has befriended Belle and her father, but trouble still abounds. She has a huge hole gaping in her roof, after all! When they take a trip to the morning market to find help, Nagi decides it is the perfect time to introduce Asa to the community. Will the giant spider be greeted with terror or a warm welcome?"--Back cover.